Microbial gatekeepers: midgut bacteria in Aedes mosquitoes as modulators of arboviral transmission and targets for sustainable vector control - Worku, Addis Temie; Sciarretta, Andrea; Guarnieri, Antonio; Falcone, Marilina; Brancazio, Natashia; Minwuyelet, Awoke; Cutuli, Marco Alfio; Atenafu, Getnet; Nicolosi, Daria; Colacci, Marco; Yewhalaw, Delenasaw; Di Marco, Roberto; et al. (Frontiers in Microbiology, 2025)
Arboviral diseases such as Dengue virus, Zika virus, Chikungunya virus, and West Nile virus pose significant global public health and economic challenges, particularly in tropical and subtropical regions. The absence of effective vaccines and sustainable vector control strategies continues to drive high morbidity and mortality rates. Symbiotic bacteria residing in the mosquito midgut can produce antimicrobial compound, stimulate the host immune response, disrupt nutrient pathways critical for pathogen development, and interfere with the pathogen’s lifecycle and dissemination. Additionally, these microbes may reduce vector reproduction and shorten the lifespan of both immature and adult stages. Genetically modified symbiotic bacteria can release effector molecules that target pathogens without harming mosquitoes. Advances in genomic and metagenomic tools have deepened our understanding of the mosquito gut microbiome. This review highlights current knowledge of gut bacteria and arbovirus interactions and explores strategies to reduce arboviral transmission. Comprehensive literature searches were conducted using global databases, including PubMed, Web of Science, and Scopus, with a focus on English-language publications.